The Freedom to Pursue Happiness: Belief in Free Will Predicts Life Satisfaction and Positive Affect among Chinese Adolescents - Li, Chunkai; Wang, Song; Zhao, Yajun; Kong, Feng; Li, Jingguang (Frontiers in Psychology, 2017)
A small amount of research has examined the association between the belief in free will and subjective well-being among Western laypersons from individualist cultures. However, no study has examined this association among participants from collectivist cultures (e.g., Eastern Asian cultures). Therefore, in this study, we explored this association among two large, independent cohorts of Chinese adolescents (N1 = 1,660; N2 = 639; high school students). The belief in free will was measured by a self-reported questionnaire (Cohorts 1 and 2) and a two-alternative forced choice question regarding the existence of free will (Cohort 2). Subjective well-being included cognitive well-being (life satisfaction) and affective well-being (positive and negative affect) in both cohorts. Data analyses indicated that a stronger belief in free will was consistently associated with higher life satisfaction and positive affect in both cohorts. Our investigation provides evidence supporting the cultural generality of the positive effects of believing in free will on subjective well-being.